2020
DOI: 10.1029/2019wr025658
|View full text |Cite
|
Sign up to set email alerts
|

An Increase in Specific Discharge With Catchment Area Implies That Bedrock Infiltration Feeds Large Rather Than Small Mountain Headwater Streams

Abstract: Mountains are a source of water for downstream areas; thus, it is important to understand the storage and discharge characteristics of steep mountain catchments. Nested catchment studies have indicated that the relation between catchment area and specific discharge during baseflow can represent mesoscale storage and discharge characteristics, but this is poorly understood. We found that baseflow-specific discharge increased with catchment size in the headwater of the Arakawa River and identified the processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 72 publications
0
18
1
Order By: Relevance
“…Shaman et al (2004), investigating low-flow specific discharge in the Neversink River watershed, USA, which is underlain by sedimentary bedrock, suggested that deep groundwater contributions increase with increasing drainage area in subcatchments smaller than a representative elementary area (REA) of 8-21 km 2 but become constant in subcatchments larger than the REA. Asano et al (2020) found an increase in baseflow-specific discharge with drainage area in a 93.58-km 2 sedimentary watershed of the Arakawa River, Japan. In addition to baseflow-specific discharge, stream and spring baseflow chemistry have been commonly used to understand groundwater dynamics across spatial scales by separating stream water into shallow and deep groundwater.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…Shaman et al (2004), investigating low-flow specific discharge in the Neversink River watershed, USA, which is underlain by sedimentary bedrock, suggested that deep groundwater contributions increase with increasing drainage area in subcatchments smaller than a representative elementary area (REA) of 8-21 km 2 but become constant in subcatchments larger than the REA. Asano et al (2020) found an increase in baseflow-specific discharge with drainage area in a 93.58-km 2 sedimentary watershed of the Arakawa River, Japan. In addition to baseflow-specific discharge, stream and spring baseflow chemistry have been commonly used to understand groundwater dynamics across spatial scales by separating stream water into shallow and deep groundwater.…”
mentioning
confidence: 87%
“…An increase in baseflow-specific discharge with area can be caused by three factors: downstream discharge of water that infiltrates into bedrock at upstream hillslopes, increase in precipitation with area, and decrease in specific discharge during storm flow with area. Asano et al (2020) examined these factors in a 93.58-km 2 Mesozoic sedimentary watershed and showed that the downstream discharge of bedrock groundwater was the main factor causing the increase in baseflow-specific discharge with area. They reported that the spatial variation in the precipitation was small (<13%), and the specific discharge during storm flow was also smallest in the subcatchment with the smallest baseflow-specific discharge.…”
Section: Differences In the Specific Discharge Scaling Relationships Between The Volcanic And Sedimentary Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of groundwater discharge along a river network is a critical scientific question that needs to be addressed to fill the scale gap between the headwater stream, downstream river, and deep groundwater flow (Wagener et al, 2021). Non-negligible amounts of water and solutes are lost through subsurface flow paths from the headwater catchment, and the deeply infiltrating groundwater usually discharges to downstream channels in basins with permeable geology (Asano et al, 2020;Egusa et al, 2016;Fan, 2019;Iwasaki et al, 2015). Thus, mapping the spatial variability of the groundwater discharge is key to understanding the changes in the stream runoff and chemistry from the headwater to downstream as well as the connectivity between local and regional groundwater systems.…”
Section: Introductionmentioning
confidence: 99%